Mo segregation-induced changes of grain boundary segregation, precipitation, and fracture behaviors in Fe–Mn–Ni–Mo maraging steel - Dong-Hyun Kim; Yoon-Uk Heo (Journal of Materials Research and Technology)
The effects of Mo pre-segregation on the changes of the grain boundary segregation, precipitation, and fracture behaviors in Fe–Mn–Ni-based maraging steel were studied by microscopic observation and First-principles calculations. TEM observations confirmed Mo's segregation at the prior austenite grain boundary after solution treatment. This pre-segregation of Mo effectively suppresses the subsequent segregation of Ni during aging at 450 °C, thereby restricting the formation of precipitates at the prior austenite grain boundary and enhancing the grain boundary strength. On the other hand, at the packet/block boundary where Mo could not be pre-segregated, the precipitation still occurs due to sufficient segregation of Mn and Ni, leading to brittle fracture at the substructure boundaries. First-principles calculations further demonstrate that the Mo pre-segregation effectively suppresses the subsequent segregation of Ni to the grain boundary. These investigations suggest that the variation in Mo's segregation behavior governs the segregation-precipitation-fracture relationship at the prior and substructure boundaries in Fe–Mn–Ni–Mo-based maraging steel.